2020
DOI: 10.3389/fphar.2020.00363
|View full text |Cite
|
Sign up to set email alerts
|

Nanobubble Mediated Gene Delivery in Conjunction With a Hand-Held Ultrasound Scanner

Abstract: Recent research has revealed that nanobubbles (NBs) can be an effective tool for gene transfection in conjunction with therapeutic ultrasound (US). However, an approach to apply commercially available hand-held diagnostic US scanners for this purpose has not been evaluated as of now. In the present study, we first compared in vitro, the efficiency of gene transfer (pCMV-Luciferase) with lipid-based and albumin-based NBs irradiated by therapeutic US (1MHz, 5.0 W/cm 2) in oral squamous carcinoma cell line HSC-2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…While destructive probes do not provide spatial information on detected cavitation, aside from that inferred from behavior and time delays, it is possible that active delivery enhances intact NB penetration into tumors under the tested conditions: Indeed it has recently been shown that targeted NBs under ultrasound exposure are able to achieve deep penetration into rabbit clots, and with greater efficacy than stimulated MBs 67 . Ultrasound stimulation of NBs has also been shown to enhance delivery and penetration of co-injected or loaded drugs in various preclinical tumor models 10 , 11 , 48 , 49 and for blood-brain-barrier disruption 7 , 8 , though intact NB extravasation was not validated and microscale events were not visualized. A plethora of ultrasound parameters have been used, typically with frequencies between 1-10 MHz, durations on the order of a few minutes, but greatly varying acoustic pressures from 100 kPa to several MPa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While destructive probes do not provide spatial information on detected cavitation, aside from that inferred from behavior and time delays, it is possible that active delivery enhances intact NB penetration into tumors under the tested conditions: Indeed it has recently been shown that targeted NBs under ultrasound exposure are able to achieve deep penetration into rabbit clots, and with greater efficacy than stimulated MBs 67 . Ultrasound stimulation of NBs has also been shown to enhance delivery and penetration of co-injected or loaded drugs in various preclinical tumor models 10 , 11 , 48 , 49 and for blood-brain-barrier disruption 7 , 8 , though intact NB extravasation was not validated and microscale events were not visualized. A plethora of ultrasound parameters have been used, typically with frequencies between 1-10 MHz, durations on the order of a few minutes, but greatly varying acoustic pressures from 100 kPa to several MPa.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous reports have begun to emerge for the formulation of stable NBs 31 - 35 with applications of conventional ultrasound contrast imaging 34 - 41 , targeted imaging 42 - 44 , and as predictive markers 40 , 45 . Several reports have further demonstrated compelling therapeutic evidence of targeted 9 - 11 , 46 - 48 and loaded 8 - 13 , 46 - 49 NBs with both passive and active (ultrasound-triggered) approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In order to maintain the bubble in a stable state for prolonged periods under ultrasound stimulation, the NB is structured as a core gas with or proteins. [62][63][64][65][66][67] In addition, polyethylene glycol (PEG) can be integrated to improve their stability, biocompatibility, and extend the circulation time in the body. 68 Although many studies have reported numerous coating strategies that can be used to stabilize NBs under ultrasound stimulation, the mechanisms underlying ultrasound interaction with NBs are still under investigation.…”
Section: Ultrasound-direct-responsive Nbsmentioning
confidence: 99%
“…71 In recent years, ultrasound-mediated gene delivery systems with nanobubbles have been developed as a non-viral vector gene delivery system that helps overcome some shortfalls of conventional viral approaches. 70,72,73 In this system, transient pores are opened, by utilizing nano and microbubbles that interact with ultrasound, to disrupt the cell membrane. As a result, these pores allow the transfer and transduction of genetic material into the host cell without the need for endocytosis (Fig.…”
Section: Tissue or Organ-selective Gene Delivery By The Combination Of Ultrasound And Nano/microbubbles Or Bubble Liposomesmentioning
confidence: 99%
“…In both groups, a signicant increase in expression of the luciferase with the use of nanobubbles and ultrasound was observed. 73 2.4.1 Plasmid DNA delivery. In vitro studies have previously been performed using the transfection method where cells suspended with microbubbles and plasmid DNA are exposed to ultrasound for up to tens of seconds.…”
Section: Tissue or Organ-selective Gene Delivery By The Combination Of Ultrasound And Nano/microbubbles Or Bubble Liposomesmentioning
confidence: 99%